A Study on Q-Fuzzy Subnearrings of a Nearring - Chitra, V.; Karmegam, Arjunan (JOURNAL OF ADVANCES IN MATHEMATICS, 2013)
In this paper, we study some of the properties of Q-fuzzy subnearring of a nearring and prove some results on these.